Control interno y su incidencia en la rentabilidad del comisariato “Cash Market” del cantón La Maná, provincia de Cotopaxi, año 2021 - Chiguano Pilatasig, Erika Vanessa (2022)
The present research was carried out in the grocery store “Cash Market” located in La Maná. Its general objective was to evaluate internal control and its impact on profitability. For this purpose, the exploratory, scientific and analytical method was used, as well as field research for the development of interviews, surveys, and the internal control questionnaire. Through the diagnosis of the current situation of internal control in the grocery store CASH MARKET carried out through interviews and surveys, the following shortcomings could be known: not having defined policies for the development of activities, maintaining almost empirical management. It was also possible to demonstrate the non-existence of the mission, and vision, in addition to the fact that profitability is not optimal. Based on the results of the comparative table, it was possible to notice the presence of deficiencies in the strategic direction, organizational structure, policies and procedures, internal control system, staff training, and supporting documentation in the operations carried out in the company; Through the evaluation of the internal control procedures through the application of the COSO I methodology, it was possible to know that the level of risk was moderate with 72% and a moderate risk with 28%. Finally, with the results obtained in the diagnostic phase and the evaluation of internal control, we proceeded to design policies and procedures for commercial activities, purchasing policies, sales policies, inventory area policies, and a flowchart of the cashier process, when applied will directly benefit the owner and collaborators of the grocery store.